Two new species of Acentrella Bengtsson, 1912 (Ephemeroptera, Baetidae) from Kazakhstan with notes on the Palaearctic fauna - Sroka, Pavel; Arnekleiv, Jo Vegar (Zootaxa, 2010)
A detailed morphological description of the larval stage of Acentrella glareosa sp. nov. and Acentrella charadra sp. nov. from the genus Acentrella Bengtsson, 1912 is given. Their differential diagnoses are provided with regard to other Palaearctic representatives of the genus. A. glareosa sp. nov. can be distinguished from the related species by the unique shape of maxillary palp, the arrangement of the bristles on it’s legs (the presence of bilateral ciliation and the second ventral row of tibial bristles) and vestigial paracercus. A. charadra sp. nov. is characterized mainly by the presence of apparent subapical bristles on the tarsal claws, the shape of it’s leg bristles (bilateraly ciliate on femora and tibiae, a row of tarsal bristles missing), the unique shape of the labial palp and vestigial paracercus. The generic concept of Acentrella and its historical development is summarized. Possible relationships of Acentrella to the Baetidae genera Liebebiella Waltz & McCafferty, 1987, Platybaetis Müller-Liebenau, 1982, Jubabaetis Müller-Liebenau, 1982 and Gratia Thomas, 1992 from the Oriental Region are discussed. A species list and synonymies of all 13 Palaearctic representatives of the genus Acentrella is presented, including the respective type localities and metamorphic stages described so far.